Analisis Perencanaan Pajak Penghasilan PPh 21 Sebagai Upaya untuk Meningkatkan Efesiensi Beban Pajak Studi Kasus Pada Persek MJH - Mohammad Affan Mantu; Achmad Ibnu Sholeh (Jurnal Pajak Vokasi (JUPASI), 2020)
Tax planning is a process of organizing taxpayer's business in such a way that its payable tax, either income or other taxes, is in minimum amount. The company can save coporate income payment by means of applying Gross Up method in estimating income tax PPh 21 but the company applied gross method. This research aims to analyze the estimation of PPh 21 used by Persek Mjayahadi & Co through the estimation of PPh 21 using Gross and Gross Up methods as well as constraints an attempts taken to save the corporate tax. The author used Chairl Anwar Pohan’s (2017:21) theoy. The research method employed was descriptive quatitative one. Techniques of collecting data used were observation, interview, and documentation. The result of research shows that total tax assumed by the employees is IDR 2,431,591,608, but following the use of gross up method, it becomes IDR 2,429,661,781, with the difference of IDR 1,929,827. Therefore, the net profit after tax subtracted wtth non-deductible burden before the application of gross Up method Is IDR 7,987,666,865, and after the appIication of gross up is IDR 7,989,596,692. Therefore, there is a difference of IDR 1,929,827, meaning equal to the tax efficiency.